Pseudoparallel invariant submanifolds of Kenmotsu manifolds - Nurnisa Karaman; Mehmet Atçeken (Journal of Amasya University the Institute of Sciences and Technology)
In this paper, we consider pseudoparallel invariant submanifolds, a particular class of invariant submanifolds of Kenmotsu manifolds, on $W_8$ curvature tensor and investigate some of their basic characterizations, such as $W_8$ pseudoparallel, $W_8$-2 pseudoparallel, $W_8$-Ricci generalized pseudoparallel, and $W_8$-2 Ricci generalized pseudoparallel. Moreover, we present some relations between these pseudoparallel invariant submanifolds and semi-parallel invariant submanifolds. We finally discuss the need for further research.